Wprowadzenie e-Votingu a zmiana zachowań politycznych na przykładzie przedstawicieli „piątej Szwajcarii” - Pazik, Aneta (Polityka i Społeczeństwo, 2021)
The article provides an insight into the realignment of voting behaviour of Swiss living abroad after the implementation of e-Voting. The canton of Geneva was selected as a case study in the article as it was one of the first to introduce online voting in Swit-zerland. In 2003 canton of Geneva together with cantons of Zurich and Neuchâtel partic-ipated in a pilot programme, the aim of which was to test e-Voting systems. A year later residents of Geneva were allowed to use online voting system in elections at cantonal and federal level. Subsequently the right was extended to other communities and in 2009 it was conferred on Swiss living abroad. The aim of the paper is to verify whether the implementation of e-Voting positively affected the turnout of citizens under consideration and if it replaced other means of voting. In the research mainly quantitative research methods were used. A statistical analysis was based on data related to voting behaviours of Swiss in period 1999–2014.